Design and analysis of composite monopole and slot antennas - Dai, Yaohui (Nanyang Technological University, 2024)
Composite antennas represent a widely studied category within the current antenna research domain, primarily due to the structural simplicity, ease of conformability, and exceptional performance of monopole and slot antennas. These characteristics frequently facilitate their combined design and application across a myriad of scenarios. This dissertation introduces two distinct new types of composite monopole slot antennas. The first type is an improved differential composite antenna, based on the foundational composite model. This variant incorporates an additional monopole and employs differential feeding, achieving an impedance bandwidth of 1.21–2.68 GHz, which corresponds to 76.5 percent, and, following modification of the slot shape, sees an increase in the gain range to 6.2 to 8.9 dBi. The second type encompasses composite antenna arrays, including Arrays A and B. Array A exhibits impedance bandwidths of 34.0 percent and 61.0 percent under standard and differential feeding conditions, respectively; while Array B, employing direct differential feeding, attains an impedance bandwidth of 1.22–2.94 GHz, equivalent to 82.7 percent, with a gain range of 11.4 to 14.4 dBi. Notably, both antenna types maintain stable radiation patterns.